Aktivitas Membran Bakiko (Bayam-Kitosan-Kolagen) terhadap Ekspresi Matriks Metaloproteinase-9 pada Luka Bakar Derajat II - Hazmi Dwinanda Nurqistan; Al Munawir; Ika Rahmawati Sutejo (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Matrix metalloproteinase-9 (MMP-9) plays an important role in regulating the degradation and deposition extracellular matrix (ECM) that are important for wound reepithelization. However, excessive protease activity can lead to delayed wound healing. Kaemferol in spinach can inhibit the activity of MMP-9. Chitosan and collagen can help tissue growth and have an antimicrobial effect. Chitosan-collagen membranes have been widely used for wound healing but, the results are unsatisfactory. Therefore, the researcher wanted to know the activity of bakiko (Spinach-Chitosan-Collagen) membrane to MMP-9 expression on second degree burn with immunohistochemical method. This research was true-experimental laboratories design with post test only control group design. The experimental animals used were 36 white wistar rats (Rattus novergicus) male, divided into 4 groups ie control group, negative control, positive control (bioplacenton), and treatment (bakiko membrane). Data were obtained by calculating MMP-9 using ImageJ software. The analysis using anova test showed that p value less than 0.05 indicated a significant difference. This study showed that there was a decrease in MMP-9 activity by bakiko membrane in grade II burn with immunohistochemical method in wistar rats.